Design a pure sinusoidal single phase inverter / Nazhirad Adam and Mohamad Habib Ismail - Adam, Nazhirad; Ismail, Mohamad Habib (2005)
DC-to -ac converters are known as inverters. The function of an inverter is to change a dc input voltage to a symmetrical ac output voltage of desired magnitude and frequency. The output voltage could be fixed or variable at a fixed or variable frequency. A variable output voltage can be obtained by varying the gain in the inverter, which is normally accomplished by pulse-width- modulation (PWM) control within the inverter. The inverter gain may be defined as the ratio of the ac output voltage to dc input voltage. In this thesis, in order to get the pure sinusoidal output we have to choose the most suitable pulse- width-modulation. This PWM will connect at the gate of the transistor (MOSFET) in the inverter circuit. Inverters use controlled turn-on and turn-off devices such as BJTs, MOSFETs, IGBTs, MCTs, SITs, GTOs or forced-commutated thyristors depending on application. Inverters are widely used in industrial applications such as variable speed ac motor drives, induction heating, standby power supplies, and uninterruptible power supplies. The input may be a battery, fuel cell, solar cell, or other dc source.